Role of ukrainian machinery industry in export diversfication - Sheiko, I. А.; Storozhenko, O. V. (ХНУРЕ, 2021)
Export diversification becomes one of the main indicator of success of foreign trade. Organisation for Economic Co-operation and Development [5] reported, that 80% of the world's value added is generated in production and trade chains, controlled by corporations.
Keywords: export diversification; foreign trade